The Views, Cognizance and Practices of Stakeholders on Implementing Cooperative Learning in Secondary Schools - Ashagre Adimasu Ayele (Universitas Bengkulu, 2021)
The aim of this study was to investigate the attitude, awareness and practices of the different stakeholders on implementing cooperative learning in secondary schools. The study was conducted on teachers, students, school principals, and supervisors in three districts of Benishangul Gumz Region. Methodologically, Focus Group Discussion (FGD), document analysis and interviews were used to gather data from the participants. As far as sampling techniques is concerned, convenient, purposive and comprehensive sampling were employed to select samples at various levels. Accordingly, 18 teachers, 3 school principals, 3 supervisors and 36 students (totally 60 participants) were taken as samples of the study. The results indicated that the teachers hold fairly positive attitude regarding cooperative learning in the schools, yet the study indicated that the teachers’ understanding the actual application of cooperative learning calls for further attention. Conversely, the actual employment of cooperative learning was less practiced in the secondary schools. For the students to be more reflective about how they work as individuals and group, they should be encouraged to plan on academic, affective and social goals for both in and off school times. Besides, the teachers at schools, supervisors and the education offices should reassess the attention given to follow-up, support and evaluation mechanisms regarding the implementation of cooperative learning.